Sharenting in digital society: exploring the prospects of an emerging moral panic - Ugwudike, Pamela (Deviant behavior, 2024)
Debates about the risks of sharenting (the practice of parents or guardians sharing information about their children online) are gathering storm in global media reports and academic discourse. This paper analyses media representations of the practice and its risks to examine whether the attributes of a moral panic can be detected. Results reveal the presence of the attributes and the reductive depiction of sharenting risks and harms as the products of situational factors, specifically the sharenters’ agency. The paper critiques this finding and argues that a consideration of broader structural conditions marked by the power and ability of social media platforms to structure information flow and diffusion is required. This is necessary to contextualize and advance understanding of risks associated with new and emerging digital cultures such as sharenting which do not necessarily constitute criminal acts but are depicted as transgressive or deviant by the media due to the capacity of embedded practices to produce crimes and broader harms.